2009
DOI: 10.1080/10826080802345051
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Participant Self-Selection for Generalizability: Who Participates in Smoking Laboratory Research?

Abstract: The generalizability of data from laboratory smoking studies using volunteer samples is debatable. We tracked potential participants from first contact with research staff through screening to study completion. We found that a minority of individuals were ultimately enrolled in the study. Failure to enroll was as often a function of participant lack of attendance at the laboratory as a function of ineligibility. With some exceptions, groups of potential participants were similar regarding demographic character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Consistent with the existing literature, we found that a lack of motivation to quit and a low level of cigarette consumption explain a large proportion of ineligibility 7 28…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Consistent with the existing literature, we found that a lack of motivation to quit and a low level of cigarette consumption explain a large proportion of ineligibility 7 28…”
Section: Discussionsupporting
confidence: 90%
“…However, they may impair the external validity of the study, since they often exclude a substantial proportion of participants, resulting in a selection bias,5 and extending the gap between research and clinical practice 6. Common exclusion criteria include age, current or past psychiatric/drug disorder, minimal levels of tobacco use and medical conditions 7. There is a risk that this selection of participants affects the results of the treatment trial for nicotine dependence 8 9.…”
mentioning
confidence: 99%
See 3 more Smart Citations